Legal mechanisms for environmental protection during armed conflict: challenges of the 21st century - Zyhrii, Olha; Rusniak, Viktoriia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article is devoted to a comprehensive analysis of the environmental consequences of the armed conflict in Ukraine and the features of their legal regulation under martial law. The relevance of the study is due to the unprecedented scale of environmental damage caused by the full-scale invasion of the Russian Federation, which creates new problems for the legal system of Ukraine and international law as a whole. Environmental security appears not only as an element of national security, but also as a global legal priority, requiring proper legal assessment, monitoring, and international response. The purpose of the study is to determine the legal principles of environmental protection regulation under martial law, analyze the current legislation of Ukraine and international legal acts, as well as identify problems in the implementation of environmental norms during armed conflict in order to develop proposals to increase the effectiveness of the legal mechanism for environmental protection.The article examines a wide range of environmental problems caused by hostilities, including disruption of microclimatic conditions, air pollution, degradation of water resources, loss of biodiversity, destruction of natural ecosystems, as well as the emergence of new environmental risks and crises. National environmental legislation is analyzed. Special attention is paid to international legal instruments – provisions of international humanitarian law, environmental conventions, UN resolutions and guiding principles that regulate the protection of the environment during armed conflicts.The study identified key problems in the implementation of legal norms in the field of environmental protection during war, substantiated the need to create an effective mechanism for assessing and recording environmental damage, supporting international cooperation in restoring the natural environment, and introducing legal liability for wartime environmental crimes. The article supports initiatives to form special platforms and damage registers to document environmental losses caused by the Russian Federation's aggression against Ukraine.